Evaluating depressive symptoms in mania: a naturalistic study of patients with bipolar disorder - Young AH (Dove Medical Press, 2015)
Allan H Young,1 Jonas Eberhard1,21Institute of Psychiatry, King’s College London, London, UK; 2Corporate Medical Affairs, H. Lundbeck A/S, Copenhagen, DenmarkObjective: This study aimed to evaluate patients with bipolar I disorder (BD-I) who have mania with depressive symptoms and who meet the new “with mixed features” specifier of the Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5).Method: This prospective, multinational, naturalistic study surveyed psychiatrists and their patients with BD-I from October 2013 to March 2014. Eligible patients had BD-I, had a (current) manic episode, and had experienced onset of a manic episode within the previous 3 months. Psychiatrists provided patient information on depressive symptoms (DSM-5 criteria); symptoms of anxiety, irritability, and agitation; suicide attempts; and physician satisfaction with treatment response. Data were stratified according to whether patients met the criteria for the BD-I “with mixed features” specifier of DSM-5 (≥3 depressive symptoms) or not, and characteristics were compared between the two subgroups. Patients also self-reported on depressive symptoms using the Mini-International Neuropsychiatric Interview module questionnaire.Results: Overall, 34% of 1,035 patients met the criteria for BD-I “with mixed features,” exhibiting ≥3 depressive symptoms during their current manic episode. This correlated with the matched patient self-reports of depressive symptoms. During their current manic episode, BD-I patients “with mixed features” had more severe symptoms of anxiety, irritability, and agitation (average composite severity score of 4.1 vs 3.4), a higher incidence of suicide attempts (38% vs 9%), and more physician dissatisfaction with treatment response (22% vs 14%), compared to patients with 0–2 depressive symptoms (all P<0.05).Conclusion: This study found that patients with BD-I “with mixed features” (ie, ≥3 depressive symptoms during a manic episode), suffered, on average, from a greater burden of disease than patients with pure mania. Improved identification of these patients may help to optimize treatment outcomes.Keywords: bipolar disorder, mania with depressive symptoms, mixed features, DSM-5